ANALISIS PEMBELAJARAN MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN DENGAN MENGGUNAKAN KURIKULUM 2013 DI SMAN 46 JAKARTA - Karlina, Elin (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2014)
This study is aimed to analyze learning of craft and entrepreneurship by using curriculum of 2013 at SMA Negeri 46 Jakarta. The method used in this study is a qualitative case study approach,. The data collection methods used are interview, direct observation, documentation, and triangulation.The problem that will be studied is learning of craft and entrepreneurship of teachers and the tenth grade students of SMA Negeri 46 Jakartawho use the curriculum of 2013 of Academic Year in 2014/2015. The teacher uses the scientific learning of learning craft and entrepreneurship by using the process of learning as follow as: observating, asking, collecting data, associating, and communicating. The teacher uses the authentic assesment by using the obseravtion and rubric. The teache uses the project based learning to teach the students so that they are active to study craft and entrepreneuship. By using the curriculum of 2013, the tenth grade students of SMA N 46 Jakarta can use their high level thinking, competency, intelligence, and skill to explore their capabillity of creating craft and entrepreneurship.Key word : learning of craft and entrepreneurship, curriculum of 2013